2017
DOI: 10.3136/fstr.23.689
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ginsenoside Compositions by High Temperature Processing under Various Soaking Conditions

Abstract: Changes in ginsenoside composition of ginseng at high temperatures (110, 130, and 150℃) under various soaking conditions (0 _ 100% ethanol solutions) were determined. The total ginsenoside contents (20.57 _ 27.99 mg/g) of heat-processed ginsengs (HG) at 110 and 130℃ were higher than raw ginseng (16.96 mg/g). Group A's ginsenosides (Rg 1 , Re, Rf, Rb 1 , Rc, Rg 2 (S), Rb 2 , Rb 3 , and Rd) decreased with increasing temperatures and decreasing ethanol concentrations, whereas those of group B (Rh 1 , Rg 2 (R), Rg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This was attributable to the physicochemical properties of ginsenosides and the characteristics of the drying methods. Firstly, researchers found that ginsenosides are thermally unstable [7,30], and the total ginsenoside content of ginseng roots decreased from 7.0 to 4.5% when the drying temperature was increased from 45 to 60 °C. This finding was in good agreement with those reported by Xiao et al [6] and Hwang et al [31].…”
Section: Comparative Study Of Different Drying Methods For American G...mentioning
confidence: 99%
“…This was attributable to the physicochemical properties of ginsenosides and the characteristics of the drying methods. Firstly, researchers found that ginsenosides are thermally unstable [7,30], and the total ginsenoside content of ginseng roots decreased from 7.0 to 4.5% when the drying temperature was increased from 45 to 60 °C. This finding was in good agreement with those reported by Xiao et al [6] and Hwang et al [31].…”
Section: Comparative Study Of Different Drying Methods For American G...mentioning
confidence: 99%